ANALYSIS OF THE USE “WHO AM I GAME” IN LEARNING DESCRIPTIVE TEXT TO INCREASE STUDENTS WRITING SKILLS OF JUNIOR HIGH SCHOOL 30 PALEMBANG - Nailah Putri, Ariqah; Veto Mortini , Asti; Pratiwi , Etty (Universitas PGRI Palembang, 2024)
The objective of this study was to investigate the impact that playing the game